PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN SALES GROWTH TERHADAP RETURN ON ASSET PADA PT ADARO ENERGY INDONESIA TBK 2013-2023 - Wenda Supriyatin; Asep Muhammad Lutfi (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of the Current Ratio, Debt To Equity Ratio, and Sales Growth on Return on Assets at PT Adaro Energy Indonesia Tbk for the 2013-2023 period. Sampling was carried out by taking 11 years of data from the 2013 to 2023 period. Method used in this research is descriptive quantitative. The research results show that the Current Ratio data partially has no effect on the Return On Assets variable. This is proven by the t count which is smaller than the t table (0.428 < 2.364) and the sig value is greater than the significance level (0.681 > 0.05). However, the Debt To Equity Ratio data partially has no effect on Return On Assets. This is proven by the calculated t which is smaller than the t table (-1.056 < 2.364) and the sig value is greater than the significance level (0.326 > 0.05). And partial Sales Growth data has no effect on the Return On Assets variable. This is proven by the small t count from the t table (2.282 < 2.364) and the sig value is greater than the significance level (0.56 > 0.05). Current Ratio, Debt To Equity Ratio, and Sales Growth simultaneously have no effect on the variable attachment to Return On Assets at PT Adaro Energy Indonesia Tbk with a calculated F value of 3.352 < 4.34 and a significance level of 0.085 which is greater than 0.05.